TiO2 – do we have to worry about it? One of the important aetiological factors in inflammatory bowel disease - Sara Jarmakiewicz-Czaja; Aneta Sokal; Jacek Tabarkiewicz; Rafał Filip (Gastroenterology Review)
TiO2 in the food industry, designated as E171, is widely used in the production of chewing gums, sweets, and icing. It is absorbed through food ingestion and the respiratory tract. There are also reports that TiO2 nanoparticles can reach the dermis through damaged epidermis. It demonstrates the ability to accumulate in some internal organs, like spleen, liver, and kidneys, depending on its size and structure. It may have pro-inflammatory, cytotoxic, and genotoxic effects. A change in the composition of the host’s intestinal microflora is also observed after exposure to high doses of TiO2. There are some differences in TiO2 intake with food around the world, but most data indicate higher consumption of this additive by children. Due to the small amount of research and the fact that most of the analyses were carried out using animal models, it is necessary to plan future observations of long-term exposure of the TiO2 molecule.